Dual H-Toeplitz operators on the harmonic Bergman space - Li, Ran; Sun, Minghao; Bing, Di (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We mainly generalize the operators K and K^* on the Bergman space to the orthogonal complement of the harmonic Bergman space, in order to define dual H-Toeplitz operators on the harmonic Bergman space and discuss the commutativity and compactness of the dual H-Toeplitz operators.